Use of flip learning to teach graphs theory in higher education - Orcos, Lara; Jordán, Cristina; Magreñán, Á. Alberto (ICERI Proceedings, 2020)
The objective of this study is to assess the opinions of the fourth year students of the subject of Graphs, Models and Applications of the degree of Computer Engineering, at the Universitat Politecnica de Valencia (UPV), about the use of flip methodology throughout videos as a didactic strategy to learn mathematical contents, so the moment in the classroom give rise to the discussion of the different concepts, to clarify doubts and to check that they have really understood about the contents studied. This also allows a good environment for debate, in which everyone can indicate how they have tried to deal with the problem, whether they have solved it correctly or not. The results show that students of the sample had very good impressions about how the use of this methodology helped them to improve several aspects related to their learning process of the subject.
Ponencia de la conferencia "12th Annual International Conference of Education, Research and Innovation (ICERI)", Seville, Spain.
Keywords: graphs; models and Applications; flip learning; higher education; mathematical didactics; WOS(2)